Spike arm swing techniques of olympics male and female elite volleyball players (1984-2021) - Giatsis, G.; Tilp, M. (Journal of Sports Science & Medicine, 2022)
In the last decades, indoor volleyball has experienced significant rule changes and a high player specialization in both sexes. Different spike attack arm swing techniques have developed which might affect performance and risk of injury. While a variety of arm swing techniques was already shown in world class beach volleyball players, it is unclear if this is also true for world class indoor volleyball. Therefore, the purpose of this study was to assess the spike attack arm swing techniques of Olympic volleyball winners and finalists (1984-2021) and to investigate possible differences between sex, playing position, scoring system, and compared to beach volleyball. Eighty-two male (M) and 85 female (F) players were assessed from video recordings from ten competitions. Five different arm swing techniques in the cocking phase (Straight, Bow-and-arrow high, Bow-and-arrow low, Snap, Circular) were classified by two experts. The most frequent technique for both sexes was the Circular (M = 40.2%; F = 38.8%), followed by Snap (M = 28.0%; F = 23.5%), Bow-and-arrow low (M = 20.7%; F = 21.2%), Bow-and-arrow high (M = 7.3% F = 11.8%), and Straight (M = 3.7%; F = 4.7%). Bow-and-arrow high and Straight techniques were significantly less used than other techniques in both sexes. There were no significant differences (p > 0.05) in arm swing techniques between sexes, playing positions, and scoring system but significant differences (p < 0.001) to beach volleyball. Although most volleyball textbooks only describe the Bow-and-arrow techniques, most of the world class indoor volleyball players used Circular and Snap arm swing techniques. Reasons for that could be the implicit knowledge of players (and coaches) regarding increased performance (ball speed) and injury prevention. Based on these results we suggest to critically revise arm swing technique training especially for young players and players with shoulder problems.